Activin A regulates growth of gastro‐intestinal epithelial cells by mediating epithelial‐mesenchymal interaction. (2nd December 2013) - Fukamachi, Hiroshi; Kato, Shinko; Asashima, Makoto; Ichinose, Masao; Yuasa, Yasuhito
<x xml:space="preserve">Abstract</x> The importance of epithelial–mesenchymal interaction on the development of gastro‐intestinal (GI) organs has been repeatedly reported, but its molecular mechanism has not been fully understood though several factors including hepatocyte growth factor and endothelin‐3 have been shown to mediate it. Activins have been demonstrated to play important roles in the regulation of organogenesis in vertebrates, but their roles in the regulation of growth and differentiation of GI organs remain to be solved. In the present study, we examined expression of activins in developing rat GI tract, and found that inhibin bA encoding activin A was specifically expressed by GI mesenchymes, while inhibin bB encoding activin B was expressed by both epithelial and mesenchymal components. We then examined the effect of activin A on the growth of fetal rat GI epithelial cells in primary culture. We found that activin A inhibited the growth of forestomach and glandular stomach epithelial cells while it stimulated the growth of colonic epithelial cells. These results suggest that activin A secreted from GI mesenchymes region‐specifically regulates the growth of attaching epithelial cells. We thus conclude that activin A mediates epithelial‐mesenchymal interaction in the developing GI tract.